Stereotypes of Japanese women in the Meiji era in Tsuda Umeko: Osatsu ni Natta Ryuugakusei - Laili, Sofiana Dwi Nur; Noviana, Fajria (Japanese Research on Linguistics, Literature, and Culture, 2025)
This study aims to identify the stereotypes of Japanese women in the Meiji era as represented in the film Tsuda Umeko: Osatsu ni Natta Ryuugakusei. The movie tells the story of Umeko’s struggle against patriarchal culture and fighting for women’s rights in Japan. This research uses a qualitative method with Roland Barthes’ semiotic approach. The object of study is the movie Tsuda Umeko: Osatsu ni Natta Ryuugakusei, with data collection conducted through listening and note-taking techniques. The analysis is based on three main concepts in Barthes’ semiotics: denotation, connotation, and myth. Through the analysis, three strong stereotypes of Japanese women in the Meiji era were found, namely: 1) women are subordinate; 2) women are dependent on men; and 3) women are given limited access to education. From these three constructions of women’s stereotypes, it can be concluded that this movie reflects the patriarchy that was deeply rooted in the Meiji era. Therefore, it is necessary to change the mindset of society so that women are no longer positioned as subordinate parties but are given the space to develop and be equal to men, both in the domestic and public spheres.